Mutual information power analysis attack of HMAC based on SM3 - Zhen WU; Min WANG; Jin-tao RAO; Zhi-bo DU; Sheng WANG; Ling-hao ZHANG (Tongxin xuebao)
A novel method of mutual information power analysis attack was proposed.The method was built on the basis of the basic principle of power analysis and the basic theory of information.For the purpose of attacking the key,the mutual in-formation values was computed using two values between the mediate variable with the power traces.An experiment was im-plemented on the algorithm of HMAC based on SM3 using this method.The experimental results show the proposed attack method is effective because the initial value of state variable can be successfully retrieved to compute the real true key.